COMPARATIVE ANTI-DIABETIC ACTIVITIES OF Lawsonia inermis, Crysophyllum albidum, Allium sativum, And Mangifera indica USED IN AFRICAN TRADITIONAL SETTINGS - Abdulfatai, Aremu; Ajakaiye, Boluwatife Ipeminogenah; Akorede, Ganiu Jimoh; Olatunji, Aishat Omobolanle; Suleiman, Yusuf Kolawole; Ahmed, Akeem Olayiwola (FUDMA Journal of Sciences, 2025)
Diabetes mellitus is one of the major endocrine illnesses affecting over 100 million individuals worldwide. medicinal plants have been used for the treatment of diabetes with little incidence of toxicity. Aim is to compare the anti-diabetic activities of Lawsonia inermis, Chrysophyllum albidum, Allium sativum and Mangifera indica in Streptozotocin induced diabetic rats. Acute toxicity study was conducted using adult female Wistar rats (n=36). The comparative anti-diabetic study involved the use of male rats (n=35) grouped into (1-7) of five rats per groups. Group 1 (Negative control), 2 (Positive control), 3 (Lawsonia inermis at 200 mg/kg), 4 (Chrysophyllum albidum at 200 mg/kg), 5 (Allium sativum at 200 mg/kg), 6 (Mangifera Indica at 200 mg/kg), and 7 (Metformin at 500 mg/kg). Methanolic extract of L. inermis C. albidum, A. sativum and M. indica were not toxic at ≤5000 mg/kg. All the extracts exhibited anti-diabetic activities by significantly reducing the blood glucose in the order of L. inermis, A. sativum, C. albidum, and M. Indica. PCV decreased significantly in C. albidum, and M. indica. RBC increased significantly in L. inermis treated group while it reduced significantly in C. albidum and M. indica. Hb concentration followed similar trends increasing significantly in C. albidum, and M. indica. Lawsonia inermis possess significant anti-diabetic activities with significant modulatory effect on haematology and biochemistry when compared to other plants.